Community-care unit model of residential mental health rehabilitation services in Queensland, Australia: predicting outcomes of consumers 1-year post discharge. (2020) - Parker, S.; Arnautovska, U.; Siskind, D.; Dark, F.; McKeon, G.; Korman, N.; Harris, M.
Abstract: Aims: Community care units (CCUs) are a model of residential psychiatric rehabilitation aiming to improve the independence and community functioning of people with severe and persistent mental illness. This study examined factors predicting improvement in outcomes among CCU consumers. Methods: Hierarchical regression using data from a retrospective cohort ( N = 501) of all consumers admitted to five CCUs in Queensland, Australia between 2005 and 2014. The primary outcome was changed in mental health and social functioning (Health of the Nation Outcome Scale). Secondary outcomes were disability (Life Skills Profile-16), service use, accommodation instability, and involuntary treatment. Potential predictors covered service, consumer, and treatment characteristics. Group-level and individualised change were assessed between the year pre-admission and post-discharge. Where relevant and available, the reliable and clinically significant (RCS) change was assessed by comparison with a normative sample. Results: Group-level analyses showed statistically significant improvements in mental health and social functioning, and reductions in psychiatry-related bed-days, emergency department (ED) presentations and involuntary treatment. There were no significant changes in disability or accommodation instability. A total of 54.7% of consumers demonstrated reliable improvement in mental health and social functioning, and 43.0% showed RCS improvement. The majority (60.6%) showed a reliable improvement in psychiatry-related bed-use; a minority demonstrated reliable improvement in ED presentations (12.5%). Significant predictors of improvement included variables related to the CCU care (e.g. episode duration), consumer characteristics (e.g. primary diagnosis) and treatment variables (e.g. psychiatry-related bed-days pre-admission). Higher baseline impairment in mental health and social functioning ( β = 1.12) and longer episodes of CCU care ( β = 1.03) increased the likelihood of RCS improvement in mental health and social functioning. Conclusions: CCU care was followed by reliable improvements in relevant outcomes for many consumers. Consumers with poorer mental health and social functioning, and a longer episode of CCU care were more likely to make RCS improvements in mental health and social functioning.